Evaluation of Discordance between 10 year Cardiovascular Risk Scores in Indian Patients presenting with Myocardial infarction - Gaikwad, Abhishek; Khan, Yasmin (Cardiology and Cardiovascular Medicine, 2019)
Background: Cardiovascular diseases are rapidly emerging as major cause of mortality and disability in India. Existing Risk Calculators for Cardiovascular Risk have not undergone appropriate validation in Indian Patients. Present Study was undertaken to compare different cardiovascular calculators for CVD risk assessment models in Indian patients presenting with first episode of myocardial infarction. Methods: This study included 150 patients presenting with first episode of myocardial infarction (MI). 10-year risk of CVD was calculated using three risk assessment models Framingham Risk score (Risk FRS), Revised American College of Cardiology/American Heart Association (Risk ACC/AHA) and WHO Risk Prediction Charts. Results: Risk FRS recognized the highest number of patients (74%) at high CVD risk (>20% 10 yr CV Risk) while Risk ACC/AHA and WHO ISH Risk calculators provided inferior risk discrimination. Risk FRS and Risk ACC/AHA had good correlation (Pearson's r 0.93, p<0.001) but poor agreement when divided into Subcategories (Kappa =0.022). Conclusion: FRS seems to be as most useful CVD risk assessment tool in identification of Indian patients at high Cardiovascular Risk.